The Effectiveness of Home Learning Among Secondary School Students in Nyakayojo Mbarara City South - Nahurira, Beatrace; Barigye, Enock; Tibanyendera, Basil (East African Journal of Education Studies, 2022)
The study assesses the effectiveness of home learning among secondary school students in Nyakayojo Mbarara City South. The researcher used a cross-sectional research design. Both quantitative and qualitative approaches were used. The population of the study comprised the Mbarara City Inspector of Schools, Mbarara City Education Officer, Students, Headteachers, Director of Studies, Chairperson LC1, and parents. A sample size of 311 respondents participated in the study. The study findings found that the effectiveness of home learning in Nyakayojo Mbarara City South was bad. It was concluded that there was the ineffectiveness of home learning in Nyakayojo Mbarara City South. It was recommended that the government should always distribute self-study materials on time. This will enable students to keep motivated while learning from home during holidays. The government should ensure that the study materials distributed are effectively utilised by students. This can be implemented through sensitisation on mass media like radios, TVs, and Newspapers, among others